In Memoriam. Waldemar Ceran (7 IX 1936 – 20 VI 2009) - Ilski, Kazimierz (Balcanica Posnaniensia. Acta et studia, 2010)
The text dedicated to the memory of the eminent Polish Byzantinologist presents his academic achievements, personality and contribution to the development of the Polish school of Byzantinology. The author presents the profile of Waldemar Ceran – from his youth in Gdańsk, through his history studies at the University of Łódź, to his long academic career associated with this centre. On the basis of his own memories and experiences, he presents the professor as a researcher and a man of wide interests – a music, sport and ancient culture fan.